Instructional Material Development Models in Arabic Language Learning: A Comparative Study - Lia Nadila Santika; Firda Nur Aliyah (Gunung Djati Conference Series, 2026)
Instructional materials play a crucial role in the effectiveness of Arabic language learning, particularly in developing listening, speaking, reading, writing skills, and utilizing interactive media (Supardi, 2020; Khain Abusyairi, 2013). This study aims to describe the characteristics, strengths, and weaknesses of several instructional material development models and determine the most suitable model for Arabic language learning. A qualitative library research method was employed, analyzing relevant books and journal articles using content analysis. The results indicate that the ASSURE model is the most suitable for regular classes due to its integration of media, technology, and active student participation; the ADDIE model is useful as a framework for planning and evaluation; the 4D model is effective for developing comprehensive modules or instructional media; and the Borg & Gall model excels in research and development based on real needs. The implications highlight the importance of selecting a model that aligns with student characteristics, learning objectives, and available resources to enhance learning effectiveness and instructional material quality.